How Does Emissions Trading Affect the Efficiency of Enterprise Resource Allocation? Evidence From China - Bing Zhou; Gong Zhang; Shulei Bi (SAGE Open, 2023)
Emission trading policies can provide environmental incentives for businesses, leading to a reduction in pollution emissions and promoting sustainable environmental development. Previous research indicated the significant impact of market-based environmental regulations on emission reduction by businesses, however, there is a lack of in-depth examination from the perspective of overall corporate management efficiency. In this study, we conducted research using the 2007 SO 2 emission trading pilot program as a quasi-natural experiment to investigate the mechanisms and effects of emission trading systems on corporate resource allocation efficiency. The study found that the implementation of emission trading systems significantly improves corporate resource allocation efficiency. Furthermore, through market regulation and administrative supervision mechanisms, corporate resource allocation efficiency can be further enhanced. However, emission trading systems have heterogeneous effects on resource allocation efficiency, with a stronger promotion effect on optimizing resource allocation in cases of greater financing constraints and higher levels of corporate governance. This study provides important policy insights for further promoting market-based environmental regulation reforms and improving corporate resource allocation efficiency.